SHORT-TERM USEFULNESS, BEHAVIORAL INTENTION, DAN USE BEHAVIOR MOBILE LEARNING SISWA SMK DI KOTA MAKASSAR - Mahande, Ridwan Daud; Malago, Jasruddin; Jasmin, Jasmin (Indonesian Journal of Educational Studies, 2015)
This study aims to identify factors that affect the use of mobile learning vocational of students in Makassar. Type of quantitative research studies nonexperimental kind of ex-post facto. These samples included 450 students of three SMK Negeri three in Makassar selected by stratified random sampling. The technique of collecting data using questionnaires and interviews. Data analysis using Structural Equation Modeling (SEM). The results showed that short-term usefulness contribute directly to the behavioral intention of 0.64 (64%) and contributed indirectly through behavioral intention to use mobile learning behavior of 0.42 (42%), while the behavioral intention to contribute directly to use mobile learning behavior of 0.66 (66%). Thus, short-term usefulness and behavioral intention to influence the level of use of mobile learning by vocational students either directly or indirectly.